Attraction Development Studies Lubuak Bonta 2x11 Kayu Tanam Sub District In Padang Pariaman District - MURDANI, TAUFIK; Rianto, M.Pd, Slamet; Yuherman, SP., M.Pd, Yuherman, SP., M.Pd (STKIP PGRI Sumbar, 2014)
ABSTRACT This research is aimed to gain an overview of the development studies Lubuak Bonta attractions in the district 2x11 Kayu Tanam Pariaman district in view of: 1) strength (strength) that have potential attraction Lubuak Bonta, 2) Weakness (weakness) constraints encountered, 3) Opportunitties (opportunities) attraction opportunities, 4) Threaths (threat) loss for tourism, 5) strategy (business) is done. This type of research is a qualitative research technique of purposive sampling determination informant who tried to reveal the development of attraction to see the strengths, weaknesses , opportunities, threats and strategies of attraction Lubuak Bonta. Data were collected through; 1) observation, 2) interviews, 3) documentation. Informants in this study is the Department of Youth Culture Sports and Tourism ( DISPORABUDPAR ) Padang Pariaman District, sub district 2x11 Kayu Tanam, Wali Nagari Kapalo Hilalang , managers, visitors and the community as much as 24 people. Based on the results of research and discussion in this study , we can conclude the following: 1 ) The power of attraction is attraction Lubuak Bonta is a public bath where the water comes from springs hills . In addition to the strength of this attraction Lubuak Bonta is a beautiful waterfall with a beautiful natural scenery. 2) Weakness possessed by Lubuak Bonta this attraction is less terawatnya attraction by the local community, the lack of cleaning bushes that interfere with the beauty of attraction Lubuak Bonta. Seen also access roads to poorly maintained attraction , the lack of public attention. 3) Opportunities owned by Lubuak Bonta attraction is nature that provides the place so it can be used as a tourist attraction. 4) Threats owned by Lubuak Bonta attraction is the event that changed public opinion so that visitors and infrequent visitors to visiting attractions Lubuak Bonta. 5) tourism development strategy is to maintain the beauty of Lubuak Bonta attraction to become more power in attraction.